Breaking Barriers: Organizational Adaptation for Effective Communication in Remote Work - Lisnawati; Anggelina, Hariyanti; Rahayu, Triwik Puji (Sinergi International Journal of Communication Sciences, 2025)
In the digital era, virtual teams have become the norm in global work environments. However, communication within these teams is often hindered by rigid organizational structures inherited from traditional office settings, especially in healthcare settings where the stakes of miscommunication are significantly higher. This narrative review explores how structural barriers and inadequate adaptation to digital communication platforms compromise interpersonal interaction and team performance. The study employs a comprehensive literature review approach, synthesizing evidence from empirical studies and theoretical models to analyze the challenges and propose strategic interventions. The results indicate that inflexible hierarchies, lack of informal communication spaces, and poor integration of collaborative technologies significantly disrupt information flow and trust-building in virtual teams. Additionally, undefined roles and insufficient digital infrastructure contribute to confusion and miscommunication. The discussion emphasizes the urgency of adopting flexible structures and policies that support real-time, inclusive, and culturally sensitive communication. The review concludes that organizations must implement adaptive work frameworks, invest in digital training, and promote leadership models that align with virtual team dynamics. Recommendations include integrating AI-enabled feedback systems, developing operational guidelines for communication platforms, and designing cross-cultural training programs. These strategies are critical to overcoming structural communication barriers and enhancing team synergy in remote and hybrid environments.